Validity and reliability of health belief model questionnaire for promoting breast self-examination and screening mammogram for early cancer detection - Che Mohamed, Norfariha; Moey, Soo Foon; Lim, Bee Chiu (Asian Pacific Organization for Cancer Prevention, 2019)
Background: Early detection of breast cancer is essential in improving overall women’s health. The researchers sought to develop a comprehensive measure that combined the basic components of the health belief model (HBM) with a focus on breast self-examination (BSE) and screening mammogram amongst women. Methods: Questionnaire items were developed following a review of the relevant literature of HBM on BSE and screening mammogram. The sampling frame for the study was Malaysian women aged 35 to 70 years old, living in Kuantan, Pahang and able to read or write in Bahasa Malaysia or English. As such, 103 women were randomly selected to participate in the study. Tests of validity using exploratory factor analysis (EFA) and reliability were subsequently performed to determine the psychometric properties of the questionnaire. Results: The EFA revealed nine factors (self-efficacy of mammogram, perceived barriers of BSE and mammogram, perceived susceptibility of breast cancer, perceived severity of breast cancer, cues to action for mammogram screening, perceived benefits of BSE, health motivation, perceived benefits of mammogram and self-efficacy of BSE) containing 54 items that jointly accounted for 74.2% of the observed variance. All nine factors have good internal consistency with Cronbach’s alpha ≥ 0.8. Fifty-four items remained in the final questionnaire after deleting 13 problematic items. The scale also showed good convergent and discriminant validity. Conclusion: The findings showed that the designed questionnaire was a valid and reliable instrument for the study involving women in Kuantan, Pahang. The instrument can help to assess women’s beliefs on BSE adoption and mammogram screening in health care practice and research.